IMPLICATION OF ENTREPRENEURIAL MINDSET IN BUILDING PSYCHOLOGICAL CAPITAL REVIEWED FROM THE INTENTION BECOME AN ENTREPRENEUR - Ahmad Zaenuri; Erwan Nur Hidayat; Erlinda Sholihah (Ekonomi dan Bisnis, 2023)
The research aims to assess entrepreneurial mindset’s effect on entrepreneurial intention through psychological capital dimensions, i.e., resilience, optimism, hope, and self-efficacy. The paper develops the Theory of Planned Behavior (TPB) concept. This is a quantitative type of research using an explanatory approach. The specified population was final students of Universities at Semarang City. The sample was randomly selected by 200 respondents using Google Forms. Then, the method of data analysis applied was SEM-PLS with SmartPLS. The authors pointed out that entrepreneurial mindset significantly affects resilience, optimism, hope, and self-efficacy. Next, resilience also affects entrepreneurial intentions. Otherwise, optimism, hope, and self-efficacy do not significantly affect entrepreneurial intentions. This theoretical study’s contribution is expected to help extend the TPB concept and solve the problems related to student’s entrepreneurial intentions. Keywords: Entrepreneurial Mindset; Psychological Capital; Entrepreneurial Intention; College Student